THE EFFECTIVENESS OF SMALL GROUP DISCUSSIONS IN THE TEACHING OF CONDITIONAL CLAUSES - Jonathan Tanihardjo; Rex Stardy (IKIP Siliwangi, 2023)
In the past, when it came to teaching grammar, it had been a common practice that teachers were the ones to more actively engage in the teaching and learning process and students only needed to pay attention to the lecture. Teachers believed it worked more effectively than other methods, since they would give many examples necessary and provide comprehensive explanation on the targeted grammar rules. However, grammar is one of the language components that are often considered challenging and relatively trivial in language learning, and for that reason, language learners are often reluctant to learn the rule of a language inside and out. Up until now, teachers have been trying to find ways or methods that might work to make learning more effective, one of which is small group discussion, where learners are expected to get more involved in a discussion, increase student participation, promote critical thinking, and so on. The participants of this study were the students of the English Department who were taking the English Grammar class. The participants were divided into 2 groups, where the first group serves as a control group and the second as an experimental group. Pre- and post-tests about the application of conditional clauses were administered to both groups to find out and measure the effectiveness of each method: lecture and group discussion methods. The results show both methods worked in boosting the students’ understanding and scores. However, lecture method worked more effectively in this study. The study also shows that getting students to actively involve in the teaching-learning process when they are not ready will not produce favourable results, as there are possible reasons that hinder the process. Keywords: Effectiveness; Small Group Discussions; Lecture; Conditional Sentences